Річковий бобер (CASTOR FIBER L.) на різних типах водойм Харківської області - Ярмак, Катерина В'ячеславівна (Харків : Харківський національний університет В. Н. Каразіна, 2018)
Об`єкт дослідження: поселення бобра річкового (Castor fiber L.) різного типу на території Харківської області. Мета: аналіз особливостей структури та динаміки поселень річкового бобра на різних типах водойм Харківської області. Методи: еколого-статистичний, уточнення меж поселення, визначення потужності поселення, морфологічний метод. Проаналізовано динаміку ареалу річкового бобра в Україні з 1853 року по теперішній час. Із 60-х рр. XX століття спостерігається процес зростання популяції, що супроводжується розширенням ареалу. Вивчено особливості структури поселень бобра на водоймах різного типу на території національного природного парку «Слобожанський», уздовж рр. Мерла, Мерчик, Уди та Лопань. Чинники, які впливають на тривалість існування та динаміку чисельності бобрових поселень, залежать від типу поселення. В поселеннях річкових русел найбільш значущими є наявність доступної деревини та присутність людини, болотного типу – рівень води, наявність і об’єм кормової бази, на озерних ¬– об’єм кормової бази та коливання рівня води. У даний час загальна кількість поселень бобра річкового у Харківській області складає мінімум 85. Визначено позитивні перспективи та спрогнозовано напрямки подальшого розселення бобра на території Харківської області.

The object of the study is the settlement of a different type of castor fiber (Castor fiber L.) in the territory of the Kharkiv region. Goal: analysis of the features of the structure and dynamics of river beaver settlements on different types of reservoirs of the Kharkiv region. Methods: ecological-statistical, specification of the limits of settlement, determination of settlement capacity, morphological method. The dynamics of the range of river beaver in Ukraine from 1853 to present time is analyzed. Since the 1960's the population growth has been observed, which is accompanied by the expansion of the range. The features of the structure of settlements of beaver in reservoirs of various types in the territory of the national natural park "Slobozhansky" along the Merl, Merchik, Udi and Lopan are studied. Factors influencing the length of existence and the dynamics of the number of beaver settlements depend on the type of settlement. In the settlements of river channels the most important are the availability of accessible wood and the presence of man, the marsh type - the water level, the availability and volume of the forage base, the lake ¬-volume of the forage base and fluctuations in the water level. At present, the total number of settlements of the river beaver in the Kharkiv region is at least 85. Positive prospects are identified and directions for further beaver settlement on the territory of the Kharkiv region are predicted.
Науковий керівник: Атемасова Тетяна Андріївна, доцент каф.зоології та екології тварин, канд. біологічних наук
Keywords: NATURAL SCIENCES::Biology::Terrestrial, freshwater and marine ecology::Freshwater ecology; NATURAL SCIENCES::Biology::Organism biology::Plant physiology; напівводні ссавці; бобер річковий; поселення; тип водойми; Харківська область; semi-aquatic mammals; river beaver; settlement; type of reservoir; Kharkiv region